(untitled) (World Science, 2020)
The article considers the problem of risk assessment in the construction project of procurement. The classification of risk assessment methods based on the completeness of information available to the researcher is given. Summary of essence simulation methods, statistical method, sensitivity analysis method, landscaping decision method, expert method and approach based on the use of fuzzy logic. A more detailed description of the assessment of environmental risks using a method based on the use of a fuzzy logic apparatus is given.